Over-the-Air Phased Array Calibration Based on the SPGD Algorithm - Wang, Xiaobin; Gong, Zhishuang; Ge, Guangding; Ma, Ji; Wang, Yong (IEEE antennas and wireless propagation letters, 2024)
Phase errors of phased array antenna (PAA) can cause pattern distortion. This letter presents an over-the-air (OTA) phased array calibration method by an iterative stochastic parallel gradient descent (SPGD) algorithm. During the measurement, all the phased array elements are excited simultaneously, and an external receiving probe is placed to a given direction in the far-field for amplitude measurement, which is used as the fitness function. The basic principle is to find the optimal phases that maximize the fitness function by gradient operation. We numerically simulated and experimentally validated in a 4 × 4 uniform rectangular array (URA) at 2.6 GHz. The experimental results show that the proposed method needs 6N∼7N measurements to calibrate an N -element PAA and its calibration accuracy is comparable to that of the well-known rotating element electric field vector (REV) method. The proposed method provides a new idea for fast and accurate OTA phase calibration for PAA.